Variance decomposition in dividend policy at three levels - Farzana Perveen; Muhammad Aksar; Ayaz Ul Haq; Shoaib Hassan (International Journal of Management, Economics and Social Sciences (IJMESS), 2020)
Dividend is an unresolved puzzle in corporate finance and present study attempted to resolve this puzzle by testing the impact of industry, firm, and firm year on dividend policy. The study applied the variance decomposition technique in order to investigate the variance in dividend payout ratios at firm year, firm, and industry level. Study used conveniently sampled data of 57 non-financial firms from 2005 to 2017. The study revealed that at firm and firm year level dividend payout ratios are varied significantly in Pakistan. However, the study found insignificant variation at industry level (measuring by dividend to cash flow and sale ratios) in dividend payout ratios. The study provides important evidence to the stakeholders about the relation of dividend policy and firm year, industry, and firm. The investors and managements need to consider the impact of firm year on dividend policy while formulating dividend policy of the Pakistani firms. Furthermore, the study adds significant contribution to the existing literature by clarifying the three important determinants of dividend policy with respect to their contribution in Pakistan.
Keywords: G35; 330; Dividend policy; variance decomposition; hierarchical linear modeling; dividend payout ratios; corporate finance